Palladium-Catalyzed Homo-Dimerization of Terminal Alkynes - Chen, Xia; Guo, Hong-Yu; Zhou, Xiao-Yu; Bao, Ming (Synthesis, 2023)
The palladium-catalyzed homo-dimerization of terminal alkynes is a powerful and atom-economic method for the preparation of highly unsaturated four-carbon skeletons, which are key structural units found in natural and/or biologically active products and materials. However, during the homo-dimerization of terminal alkynes, a major issue is control of the chemo-, regio-, and stereoselectivity. Thus, over the past few decades, various strategies and methods have been developed that employ palladium catalytic systems for such homo-dimerizations. In this Short Review, we highlight important methods for the selective synthesis of these valuable four-carbon compounds, including conjugated 1,3-enynes, 1,3-diynes, and 1,3-dienes.1 Introduction2 Redox-Neutral Homo-Dimerization of Terminal Alkynes for the Synthesis of 1,3-Enynes2.1 Head-to-Head Dimerization2.2 Head-to-Tail Dimerization3 Oxidative Homo-Dimerization of Terminal Alkynes for the Synthesis of 1,3-Diynes3.1 Unsupported Palladium Catalysts3.1.1 Choice of Oxidant3.1.2 Choice of Ligand3.1.3 Choice of Solvent3.2 Supported Palladium Catalysts4 Reductive Homo-Dimerization of Terminal Alkynes for the Synthesis of 1,3-Dienes5 Conclusion
Keywords: homo-dimerization; terminal alkynes; palladium catalysis; unsaturated four-carbon skeletons; selectivity